2019
DOI: 10.1093/jxb/erz231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into the modification of the pre-fertilization mechanisms during plant domestication

Abstract: Plant domestication is the process of adapting plants to human use by selecting specific traits. The selection process often involves the modification of some components of the plant reproductive mechanisms. Allelic variants of genes associated with flowering time, vernalization, and the circadian clock are responsible for the adaptation of crops, such as rice, maize, barley, wheat, and tomato, to non-native latitudes. Modifications in the plant architecture and branching have been selected for higher yields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…Another trend is that all taxa appear to have both repressors and promoters of flowering that are active under both long and short days. This suggests that photoperiod has been an important cue for flowering throughout the lifespan and range of the grass family, as is observed at the cultivar level in most cereal crops (Liu et al, 2015;Manrique et al, 2019).…”
Section: Photoperiod Is the Most Stabile Seasonal Cue In A Changing Climatementioning
confidence: 80%
“…Another trend is that all taxa appear to have both repressors and promoters of flowering that are active under both long and short days. This suggests that photoperiod has been an important cue for flowering throughout the lifespan and range of the grass family, as is observed at the cultivar level in most cereal crops (Liu et al, 2015;Manrique et al, 2019).…”
Section: Photoperiod Is the Most Stabile Seasonal Cue In A Changing Climatementioning
confidence: 80%
“…We however did not use stigma tests to investigate the behavior of the self-pollen on these three cultivars, preventing us to conclude on the reason of self-crosses (i.e., self-compatibility mutation vs. leaky self-incompatibility). Selfing in cultivated olives could indeed result from the artificial selection of self-compatible mutants over millennia, particularly via their vegetative propagation (Manrique et al, 2019;McKey, Elias, Pujol, & Duputié, 2010;Rowlands, 1964). Recurrent admixture events between divergent olive gene pools (East vs. West;Besnard, Terral, & Cornille, 2018) may also result in a huge phenological variation in the mating system of the cultivated olive, and more frequent selfing is expected in admixed individuals (as shown for instance in hybrids of ash trees and beets; Arnaud, Fénart, Cordellier, & Cuguen, 2010;Gérard, Klein, Austerlitz, Fernández-Manjarrés, & Frascaria-Lacoste, 2006).…”
Section: On the Diallelic Self-incompatibility System (Dsi) In Olivesmentioning
confidence: 99%
“…Every crop that we know today has already been radically modified from how it originally appeared in the wild. In this issue Manrique et al (2019) describe the remarkable domestication processes that have led to alterations in the reproductive mechanisms of plants. Studies have revealed how domestication has affected many species at the genetic and molecular levels, demonstrating that humans have long been influencing the genetic modification of plants.…”
Section: In the End It’s All About Seeds And Fruitsmentioning
confidence: 99%